Propuesta del mejoramiento del proceso productivo en la Granja La Vega , utilizando lean manufacturing (2023)
The present work was performed at the Poultry Farm La Vega, located at the vereda Villa Nueva in the town of Santa Rosa de Viterbo (Boyacá), which focuses on the production and marketing of eggs. This proposal aims to improve the productive process by making use of Lean Manufacturing tools, whose main objective is the productivity increase through optimization of time, routes and movement. The work was developed through different stages, one of them being diagnostics, where flowcharts and current farm distribution are designed. Also, a time study with a cursograma is made with the aim of establishing times and activities that were followed. Once the diagnostic is complete, another stage is identified, in which different modifications are made within the process by using Lean Manufacturing, which will allow to correct deficiencies and problems. This will be shown through the design of an implementation proposal of the philosophy of Lean Manufacturing